On the violation of CHSH inequality - Neo, Yiming (2016)
The Bell's inequality is derived under assumption of the local hidden variable models. Therefore all non-entangled particles satisfy Bell's inequality, as I will briefly argue. However, bi-partite entangled states can violate Bell's inequality. It has been shown to be true for bi-partite maximally entangled states. I will rederive this so-called Gisin's theorem, in a slightly di erent way.